Diagnostic accuracy of Xpert ultra for childhood tuberculosis: A preliminary systematic review and meta‐analysis. (25th January 2022) - Signorino, Claudia; Votto, Martina; De Filippo, Maria; Marseglia, Gian Luigi; Galli, Luisa; Chiappini, Elena
Abstract: Diagnosis of childhood tuberculosis (TB) is challenging. Xpert MTB/RIF and the new version Xpert MTB/RIF Ultra (Ultra) are molecular tests currently used to rapidly identify the infection. We reviewed the literature for the accuracy of Ultra assay in the diagnosis of tuberculosis and rifampicin resistance in children. We conducted a full search in PubMed, Web of Science (WOS), Embase, and Scopus, up to April 2021. A bivariate random‐effects model was used to determine the pooled sensitivity and specificity of Ultra, with a 95% confidence interval (CI), compared with culturing and the composite reference standard (CRS). In the ten included studies (2, 427 participants), the pooled Ultra sensitivity and specificity, in diagnosing pulmonary tuberculosis (PTB), were 78% (95% CI, 73–82) and 92% (95% CI, 91–94), respectively, against culture. Since a high heterogeneity was found between studies, we created subgroups based on different samples and ages. Ultra‐pooled sensitivity was consistently lower against CRS (95% CI, 35%, 32–38). Compared to Xpert MTB/RIF, Ultra sensitivity tended toward higher values (Ultra: 73%, 67%–78% vs. Xpert MTB/RIF: 66%, 60%–72%), but specificity was lower (Ultra: 95%, 94%–96% vs. Xpert MTB/RIF: 99%, 98%–99%). Ultra has improved the definitive diagnosis of PTB, particularly in subjects with paucibacillary TB, including children. The lower specificity could be due to the fact that culture is an imperfect reference standard. Further studies are needed to evaluate the accuracy of Ultra in the diagnosis of childhood TB.